II Certamen Crono-Teatro (2014). Modalidad de vagón 4. Nobleza obliga - Pygmalión (Pygmalion. Revista de teatro general y comparado, 2025)
II Certamen Crono-Teatro (2014). Modalidad de vagón 4. Nobleza obliga